The Creation of A Three-Tier Multiple-Choice Diagnostic Test Instrument to Identifying High School Students' Misconceptions Regarding Biological Virus Material - Sulistyoningrum, Puji; Ismail; Ali, Alimuddin (Jurnal Pijar Mipa, 2024)
This study aims to develop a diagnostic test instrument with three tiers focusing on viral material. Research and Development (R&D) constitutes a form of applied research. The participants for the Field Test were Class X students at SMAN 22 Bone, while those for the subsequent test were Class X students at SMAN 19 Bone. Interviews and documentation serve as the primary research methods employed in this study. A three-tier multiple-choice format is characterized by three levels of questioning within the multiple-choice framework. The resultant diagnostic test instrument comprises three tiers: the first tier includes questions, the second tier offers alternative explanations, and the third tier assesses respondents' confidence levels in selecting answers and providing justifications. The outcomes of this research include answer keys, test questions, and question grids as integral components of the instrument. This study demonstrates the validity of the developed instrument through validation conducted by expert validators. The reliability test yielded a robust average value of 0.91. Only 24 out of the 40 questions were deemed valid during the field test phase. Findings revealed that students exhibited an average misconception rate of 47.2%, spanning two indicators derived from the 40 questions. Notably, misconceptions were prominent in the discussion sub-topic concerning the earliest discovery of viruses and methods for distinguishing viruses and bacteria, with an average misconception rate of 56.8% in viral material. Developing a three-tier diagnostic test effectively identified students' misconceptions regarding viral material, indicating suitability and efficacy for educational application.